Plasmid Content and Tumor Initiation Complementation by Agrobacterium tumefaciens IIBNV6 - Lippincott, Barbara B. (1977)
Avirulent strains IIBNV6 and NT1, derived from virulent strains of Agrobacterium tumefaciens, were tested for their ability to enhance tumor initiation (complement) on coinoculation with tumorigenic strains. Strain NT1, cured of the Agrobacterium virulence plasmid, failed to complement when inoculated with its virulent parental strain or with other virulent strains. Strain IIBNV6, however, complemented with all virulent strains tested. Attachment to host wound sites by both strain IIBNV6 and the virulent strain was essential for this effect. Inoculation of the tumorigenic strain at different times on leaves previously inoculated with IIBNV6 showed that the capacity to complement is lost during the period between 4 and 8 h after IIBNV6 inoculation. The rate of tumor appearance obtained with an inoculum containing IIBNV6 and a virulent auxotrophic strain was characteristic of the appearance rate obtained with prototrophic bacteria. Evidence is summarized which suggests that strain IIBNV6 can induce tumors when supplied with a substance produced or induced by a virulent bacterium at a separate site. A deoxyribonucleic acid plasmid about 40% the size of the Agrobacterium virulence plasmid was obtained from strain IIBNV6. We propose that this plasmid accounts for the ability of strain IIBNV6 to complement and that it contains part of the genetic information necessary for tumor initiation.